The Effectiveness of Regional Representative Councils: An Analysis of Checks and Balances and the Protection of Indigenous Peoples Rights - Hafiz, Muhammad; Febiani, Reza Ajeng (Fakultas Syariah INSURI Ponorogo, 2025)
Following the reform, the establishment of the House of Regional Representatives (DPD) is a crucial component of the revitalization of the Indonesian constitutional system. This study examines the role of DPD in the bicameral system, as well as the regulations governing its authority in relation to the DPR, particularly in the formation of laws related to regional autonomy and indigenous peoples. The method used is normative legal research with a legislative approach. The results showed that, although DPD has a limited legislative function as stipulated in Article 22D of the 1945 Constitution, its authority has not been balanced with that of the DPR, thus hampering the effectiveness of regional representation. This imbalance has an impact on the weak protection of the aspirations of indigenous peoples, who are often victims of development policies, such as in the case of the eviction of customary land due to the construction of the Archipelago Capital. In this context, DPD should act as a bridge between the region and the central government. However, the absence of clear regulations regarding the form of DPD's accountability makes its position less optimal. Therefore, constitutional strengthening and regulatory reform are necessary to enhance the effectiveness, equality, and capacity of the DPD in representing and legislating, thereby ensuring justice, protecting the rights of indigenous peoples, and promoting equitable national development.